Sustainability in America's cities creating the green metropolis - Slavin, Matthew I.; SpringerLink (Online service). (Washington Island Press, 2011)
Sustainability" is more than the latest green buzzword. It represents a new way of viewing the interactions of human society and the natural world. Sustainability in America's Cities highlights how America's largest cities are acting to develop sustainable solutions to conflicts between development and environment. As sustainability rises to the top of public policy agendas in American cities, it is also emerging as a new discipline in colleges and universities. Specifically designed for these educational programs, this is the first book to provide empirically based, multi-disciplinary case studies of sustainability policy, planning, and practice in action. It is also valuable for everyone who designs and implements sustainability initiatives, including policy makers, public sector and non-profit practitioners, and consultants. Sustainability in America's Cities brings together academic and practicing professionals to offer firsthand insight into innovative strategies that cities have adopted in renewable energy and energy efficiency, climate change, green building, clean-tech and green jobs, transportation and infrastructure, urban forestry and sustainable food production. Case studies examine sustainability initiatives in a wide range of American cities, including San Francisco, Honolulu, Philadelphia, Phoenix, Milwaukee, New York City, Portland, Oregon and Washington D.C. The concluding chapter ties together the empirical evidence and recounts lessons learned for sustainability planning and policy.
Foreword -- Acknowledgments -- Chapter 1. The Rise of the Urban Sustainability Movement in America; Matthew I. Slavin -- Chapter 2. Strategic Climate Action Planning in Portland; Matthew I. Slavin and Kent Snyder -- Chapter 3. Greening the Industrial District: Transforming Milwaukee?s Menomonee Valley from a Blighted Brownfield into a Sustainable Place toWork and Play; Christopher De Sousa -- Chapter 4. Phoenix, the Role of the University, and the Politics of Green-Tech; Jonathan Fink -- Chapter 5. LEED in the Nation?s Capitol: A Policy and Planning Perspective on Green Building in Washington, D.C.; Gerrit Knapp, Amy E. Gardner, Ralph Bennett, Madlen Simon, and Cari Varnier -- Chapter 6. The Greening of Mobility in San Francisco; Aaron Golub and Jason Henderson -- Chapter 7. Wind, Waves, and Watts: Creating a Clean Energy Future for Honolulu; Matthew I. Slavin, Douglas A. Codiga, and Jason J. Zeller -- Chapter 8. Clean Waters, Clean City: Sustainable Storm Water Management in Philadelphia; Lynn Mandarano -- Chapter 9. Toward a Sustainable New York City: Greening through Urban Forest Restoration; P. Timon McPhearson -- Chapter 10. Greening the Food Supply in New York; Nevin Cohen and Jennifer Obadia -- Chapter 11. Where Sustainability Stands Now: Contemporary Trends and Future Prospects; Matthew I. Slavin -- References -- Contributors -- Index.
Electronic reproduction.
Keywords: Urban ecology (Sociology) -- United States; Urban policy -- United States; City planning -- Environmental aspects -- United States; Urban ecology (Sociology) -- United States -- Case studies; Sustainable urban development -- United States; Electronic books